Effects of kefir fermented with or without 1% autolyzed yeast powder on dry matter intake, intestinal permeability, and rumen fermentation profile of Holstein calves - C.A. Reynolds; S.Y. Morrison (Journal of Dairy Science)
ABSTRACT: Co-fermenting kefir with Saccharomyces cerevisiae has been shown to enhance the exopolysaccharides (EPS) produced by lactic acid bacteria during fermentation, which may further promote intestinal development in the calf. Four different concentrations (0%, 0.25%, 0.5%, and 1%) on a weight/weight basis (g/20 g kefir grain) of either dried, activated distillers yeast or autolyzed yeast powder were evaluated for EPS optimization in kefir, and inclusion of 1% autolyzed yeast powder resulted in the greatest EPS yield. In a randomized, complete block design, 81 Holstein heifers were enrolled at 3 d of age, blocked by birth weight, and randomized within block to receive either 125 mL of salable whole milk (CON), 125 mL of kefir (KEF), or 125 mL of kefir fermented with 1% autolyzed yeast powder (YAK) in milk replacer 1×/d until 28 d of age. Feed intake and health scores were recorded daily for each calf through 1-wk postweaning (63 d of age). Growth measurements were recorded weekly until 9 wk. Indigestible markers d-mannitol and Cr-EDTA were administered at 15, 29, and 50 d to a subset of calves (n = 36) and recovered in plasma and serum to measure intestinal permeability. Rumen fluid was collected from calves (n = 35) via gastric tube at 63 ± 2 d to measure pH and VFA concentrations, as well as serum BHB at 14, 28, 42, 56, and 63 d. Although health outcomes (diarrhea, respiratory illness, dehydration) were not affected by treatment, supplementation with YAK significantly improved starter DMI and BW in the preweaning period compared with CON and KEF, and postweaning DMI was significantly improved in both KEF and YAK compared with CON. Increased butyrate was observed in rumen fluid of calves fed YAK, although serum BHB was not affected. This work contributes to further understanding kefir as a promoter of gastrointestinal development in calves and the potential benefits of EPS in the developing ruminant.